Digital libraries, repositories and documents - Food and Agriculture Organization of the United Nations; Technical Centre for Agricultural and Rural Cooperation (CTA / FAO, 2010)
This e-learning module forms part of the Information Management Resource Kit (IMARK) and covers processes relevant to the creation and management of digital libraries and repositories. Providing a total curriculum of 40 self-paced lessons, grouped into eight units, it includes digital file formats, metadata management, database management and the preservation of digital information.